Informal Language and Sentiment Analysis in Brooklyn Rap Style: A Study of Ageng Carlitos' Instagram Videos - Meghna Nayda Salsabila; Dwi Ario Fajar; Sattra Sahatsathatsana (FKIP, Universitas Palangka Raya, 2026)
The use of informal language has become increasingly common in social media communication, especially among content creators who aim to make their content more engaging and relatable. This study aims to analyze the types and functions of informal language used in Ageng Carlitos’ Instagram videos and to examine viewers’ responses through sentiment analysis. This study employed a descriptive qualitative method. The data were collected from two Instagram videos, “Warung Es Cekek Asli Brooklyn” and “Stereotype”, along with viewers’ comments. The findings revealed five types of informal language: slang, contractions, abbreviations, colloquial expressions, and simplified grammatical structures. Slang was identified as the most frequently used type and reflected the characteristics of the Brooklyn rap style. The analysis also showed that informal language served several communicative functions, such as creating a friendly atmosphere, simplifying communication, and attracting viewers’ attention. In addition, the sentiment analysis indicated that positive comments dominated viewers’ responses, suggesting that Ageng Carlitos’ conversational style successfully increased viewers' interest and helped them understand the intended messages. Therefore, informal language can be considered an effective strategy for delivering English-learning content through social media.